PROFESIONALISME KEPALA SEKOLAH DALAM PENGELOLAAN PENDIDIKAN UNTUK MEWUJUDKAN SEKOLAH EFEKTIF - Oktarina, Nina (Dinamika Pendidikan, 2009)
The development of technology and science have to be harmonious with good human resources quality. One ways to reach it is education. The head master as school manager have to professionalism to manage the school. The head masterÃ¢â¬â¢s professionalism very important to build an effective school. Key words: The head masterÃ¢â¬â¢s professionalism, an effective school.